The hidden history of the American Film Institute: the cold war, arts policy, and American film preservation - Real, Brian (The Moving Image: The Journal of the Association of Moving Image Archivists, 2018)
The American Film Institute (AFI) presently does relatively little in terms of film preservation, but its founding in 1967 led to the growth of many of the mechanisms that define the motion picture preservation community today. As this article reveals, the AFI's success in promoting ongoing federal government support for motion picture preservation cannot be separated from the political context of the Cold War. The AFI's first director, George Stevens Jr., had previously been the head of the Motion Picture Service of the United States Information Agency (USIA). This work with a public diplomacy agency was essential to his vision for the design and structure of the AFI. Likewise, the AFI was founded as an independent nonprofit, but with the promise of significant ongoing funding support from the National Endowment for the Arts (NEA). While this arrangement worked well at first, a change in presidential administrations and design flaws in the AFI's support mechanisms led to it being unable to meet the expectations of the very film preservation community it helped to foster.
Keywords: dept.ils; peer-reviewed